Relationship between selected fitness components of Sarawak tennis players/ Mohamad Amirul Zaini - Zaini, Mohamad Amirul (2017)
The purpose of the study was to develop and measure the fitness components of Sarawak tennis players. Thirteen young trained players in the age bracket 15 to 21 years old with experience of at least 2 years in playing tennis and have participated in at least SUKMA level were tested for eight fitness tests. A Pearson correlation test was conducted to examine the relationships among the variables. Significant correlations were found between all the variables (p < .05) except for, flexibility and muscular strength, muscular endurance, muscular power, agility, and speed endurance (p > .05). Muscular strength for the left hand was not significantly correlated with speed and aerobic capacity (p >.05). There was no significant relationship between speed and muscular power, agility and speed, muscular endurance and aerobic capacity (p >.05). Additionally, Speed and speed endurance showed no significant relationship with muscular endurance (p > 0.5). This study quantifies physical fitness profile using the tennis-specific tests that can help to upgrade Sarawak tennis players’ performance by examining the relationships among all the fitness components. The findings would be beneficial for coaches to assess their trainees in tennis sports as well as be used as the guidelines for selection purposes.